A HISTORICAL OVERVIEW AND STUDY OF THE AESTHETIC PHILOSOPHY OF WESTERN MUSIC - Wang, Yan (European journal for philosophy of religion, 2023)
In this study we have taken the responses of 30 students and collect the data and summaries in tables and charts form. Then the reliability of Questionnaire is above 0.7 which is reliable for our study Excellence is a psychological and fundamental characteristic that is intimately linked to the tangible elements in our environment. Nature is the expert key to feeling this feeling, which will induce relative levels of excellence alongside our sentiments and feelings. Design is shaped in three layered formats in the material world and is more level headed than other expressions; at the end of the day, its relationships In the material world, there are more things than any other expression. However, music can only be framed on one side and one level in a specific time and is free of spatial constraints. Along these lines, music craftsmanship takes time to develop and is more intellectual than painting, as well as more visible than design, model, and painting. Clearly, engineering has a unique connection between the material and the unearthly worlds, according to this substance. Design has a meaningful meaning, especially beyond the material world Islamic mosques and consecrated expressions; in light of the fact that in the hallowed expressions, privileged insights are unadulterated as they frequently have no external shapes and they become an image of an Islamic conviction and a mysterious picture, the change is performed to adjust a picture with strict convictions.